Integrated geophysical investigation for pavement failure along a dual carriage way, Southwestern Nigeria: a case study - Adesola, Akinola M.; Ayokunle, Akinlalu A.; Adebowale, Adelusi O. (Kuwait Journal of Science, 2017)
An integrated geophysical investigation was carried out on some portions of Ogbomoso-Ilorin dual carriage way located within the Basement Complex area of Southwestern Nigeria, with a view to delineating the cause(s) of road pavement failure observed along the road. Three failed portions and one control stable segment of the road pavement were investigated within the southwestern flank of the road. Very-low-frequency (VLF) electromagnetic (EM) and ground magnetic measurements were carried out at a regular station interval of 5 m along traverses established parallel to the road pavement. Vertical electrical sounding (VES) using Schlumberger array and 2-D resistivity imaging using dipole-dipole electrode array were employed for the electrical resistivity method. The results of the study showed that the near surface subsoil on which the road pavement is founded within the failed segments is predominantly characterized by low resistive materials (<100 Ωm) which are typical of incompetent clay formation. The subsoil on which the road pavement is founded at the control stable segment is found to also compose of relatively low resistivity values (<150 Ωm). Major geologic features which are typical of fractures, faults, joints and cavities/voids were identified from the 2D resistivity structures on the unstable segments, classified stable segments and control stable segment. Therefore, the geological factors responsible for the susceptibility of the road to failure are clayey subgrade soil beneath the road pavement, lateral inhomogeneity, near surface geological structures and changes in elevations due to fluctuation in the saturated zone. Key Words: Pavement Failure, Lateral Inhomogeneity, Subgrade